The influence of pH and chemical composition of beverages on color stability of a nanofilled composite resin - Dias, Hercules Bezerra [UNESP]; Carrera, Emanuelle Teixeira [UNESP]; Rastelli, Alessandra Nara De Souza [UNESP] (My University, 2016)
Due to increasing consumer knowledge about the health benefits associated with anthocyanin-rich foods and beverages-such as acai and blueberry juices-The growing consumption of these products should be a source of concern for dentists. Since anthocyanins are colorants that can discolor teeth and restorations, the aim of this study was to investigate the staining effects of 2 anthocyanin-rich beverages on a nanofilled composite resin. Specimens were prepared, separated into 3 groups, and immersed in either artificial saliva or 1 of the 2 staining solutions (blueberry or acai juice) at 37C for 7 days. The color stability of the resin was significantly affected by both the storage times (P < 0.001) and the solutions (P < 0.001). The blueberry juice, which had the lowest pH level, had the greatest effect on color stability and changes in lightness of the composite resin (ΔE∗ = 14.71; ΔL∗ = -8.25; P < 0.001), followed by acai juice (ΔE∗ = 10.21; ΔL∗ = -8.77; P < 0.001) and artificial saliva (ΔE∗ = 1.36; ΔL∗ = -0.44; P < 0.001). In the present study, a nanofilled composite resin did not exhibit color stability when exposed to acai and blueberry beverages.
Keywords: Beverages; Coloring agents; Composite resins; Pigmentation